A digitális világ és az okoseszköz-használat befolyása a gyermekek kommunikációjára - Csopák Éva; Чопак Єва; Chopak Yeva; Ködöböc Orsolya; Кедебец Оршоя (Видавництво «Код», 2025)
Резюме. Метою нашого дослідження було з’ясувати, наскільки поширене використання ґаджетів у житті дітей дошкільного віку, для яких видів діяльності вони застосовуються, а також як батьки оцінюють вплив цифрових технологій. У ході дослідження ми проводили групові заняття та клінічні інтерв’ю з дітьми та їхніми батьками. Згідно з отриманими результатами, перші контакти з ґаджетами з’являються вже у 2–3 роки, а їх використання стає повсякденним, насамперед у рамках дозвіллєвих занять – перегляду мультфільмів та ігор. Відповіді дітей і батьківські інтерв’ю однаково підтвердили цю тенденцію.

Abstract. The aim of our research was to explore the extent to which smart device use is present in the lives of preschool-aged children, the activities for which these devices are applied, and parents’ perceptions of their impact on children’s development. We conducted group activities and clinical interviews with both children and their parents in order to gain a complex picture of device use in early childhood. Our findings indicate that contact with smart devices occurs as early as 2–3 years of age, and their use soon becomes integrated into children’s everyday lives. Device use was reported as being almost daily, particularly during leisure time, with children showing a clear preference for entertainment-related activities such as watching cartoons and playing games. Children’s responses consistently demonstrated a high level of familiarity with various digital devices, including smartphones, tablets, and computers, which they reported using actively and confidently. Parental interviews confirmed this trend, indicating that smart device use in this age group is not an occasional phenomenon, but rather a routine aspect of family life. While the children’s accounts highlighted the enjoyment and engagement associated with device use, the parents provided more nuanced perspectives. Some parents emphasized the potential benefits of smart devices, such as the enrichment of vocabulary, stimulation of curiosity, and opportunities for foreign language acquisition, particularly through exposure to digital storytelling. At the same time, several parents expressed concerns regarding the possible negative consequences of excessive use, such as reduced social interaction, weakened emotional regulation, and limitations in the development of communication skills. Taken together, these findings underscore both the opportunities and the risks associated with early smart device use. On the one hand, digital technologies may support cognitive and linguistic development; on the other, unregulated and excessive use may hinder children’s balanced growth. Therefore, our results point to the importance of conscious and supervised device use, guided by clear rules and age-appropriate content. Furthermore, it is essential to provide children with alternative activities–such as reading, drawing, or interactive play-that can complement digital experiences and foster holistic development. Our study thus contributes to the growing body of literature on digital childhood by highlighting the dual role of smart devices in shaping children’s communication and overall development.

Az okoseszköz-használat társadalmi és pedagógiai aktualitása. Az okoseszközök olyan digitális eszközök, amelyek egyszerű vagy összetettebb funkciókkal könnyítik meg mindennapi tevékenységeinket. Ezek képesek csatlakozni a körülöttünk lévő hálózathoz vagy egymáshoz, így lehetővé téve a kommunikációt és az adatcserét. Amikor okoseszközökről beszélünk, akkor általában vezetékes vagy vezeték nélküli hálózatra csatlakoztatott készülékekről van szó, amik képesek egymással kommunikálva egyszerűbb vagy összetettebb folyamatokat elvégezni, mindezt pedig úgy, hogy a folyamatok nagy részéről a felhasználónak nem is kell tudomást vennie. Az okoseszközök lehetnek kijelzős vagy kijelzős nélküli szerkezetek is, amik például az emberi hangra reagálnak [2]. A kutatási probléma felvetése és elméleti háttere. Az alfa generációba tartoznak azok a gyermekek, akik 2010 után születtek. Kapcsolatuk a digitális világgal már igen korai életszakaszukban kezdődik, gyakran már az anyaméhben. Ezek a gyerekek már a magzatkorban jelen vannak a közösségi média felületein, hiszen szüleik már akkor megosztják velük kapcsolatos élményeiket, még mielőtt megszületnének.
Цифрового світу та використання ґаджетів на комунікацію дітей
The influence of the digital world and smart device use on children’s communication skills
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: okoseszközök; óvodáskorú gyermekek; beszédfejlődés; szülői attitűdök; використання ґаджетів; діти дошкільного віку; мовленнєвий розвиток; використання медіа; батьківські установки